Development of an advanced nano-satellite (VELOX-I) - power management system - Hong, Charlin Zhanlin. (2013)
The objective of this Final Year Project is to develop and enhance the current Power Management System (PWRS) of the nano-satellite, VELOX-I, which is being developed by the Satellite Research Centre of Nanyang Technological University. The function of the PWRS is to manage and distribute power to the other subsystems efficiently. This is analogous to the function of a heart in the human body. Therefore, an efficient PWRS would ensure a ‘healthy’ and successful operation of the satellite.